Obstetric and perinatal outcomes in pregnancies with isolated foetal congenital heart abnormalities. (17th September 2019) - Liu, Cathy; Lodge, Jade; Flatley, Christopher; Gooi, Alexander; Ward, Cameron; Eagleson, Karen; Kumar, Sailesh
Abstract: Objective: To determine obstetric, intrapartum, and perinatal outcomes for pregnancies with isolated foetal congenital heart defects (CHDs). Methods: This was a retrospective cohort study of women that delivered an infant with an isolated major CHD between January 2010 and April 2017 at a major Australian perinatal centre. The study cohort was compared with a cohort of women with infants without CHD. Cardiac abnormalities were broadly subdivided into the following five categories using the International Classification of Diseases Tenth Revision (ICD-10) as a guide – transposition of the great arteries (TGA), septal defects, right heart lesions (RHL), left heart lesions (LHL), and "other". Demographic characteristics and obstetric, intrapartum, and perinatal outcomes were compared between the two cohorts. Results: The final study cohort comprised of 342 infants with isolated CHD and 68, 911 controls. Of the infants with CHD, 20.4% (70/342) had transposition of the great vessels, 23% (79/342) had septal lesions, 14.6% (50/342) had right sided lesions, 23.3% (80/342) left sided, and 18.4% (63/342) categorised as "other". Women with foetal CHD had a higher BMI and had higher rates of cardiac disease, diabetes mellitus, and hypertension, be smokers and consume alcohol compared to controls. The CHD cohort had lower odds of spontaneous vaginal delivery (SVD) (OR 0.73, 95%CI 0.58–0.90) and higher odds of caesarean for nonreassuring foetal status (aOR 1.65, 95%CI 1.07–2.55), birth weight <5th (aOR 3.44, 95%CI 2.38–4.98) and <10th (aOR 2.49, 95%CI 1.82–3.40) centiles, neonatal intensive care unit (NICU) admission (aOR 109.14, 95%CI 74.44–160.02), severe respiratory distress (aOR 2.90, 95%CI 2.33–3.76), 5 minutes Apgar score <7 (aOR 2.48, 95%CI 1.46–4.20), severe acidosis (aOR 1.80, 95%CI 1.14–2.85), stillbirth (aOR 4.09, 95%CI 1.62–10.33), neonatal death (aOR 24.30, 95%CI 13.24–44.61), and overall perinatal death (aOR 13.42, 95%CI 8.08–22.30). Infants with TGA had the lowest overall risk of complications whilst infants with RHL, LHL, and "others" had the highest risk of adverse outcomes, particularly death. Conclusion: Infants with CHD have overall worse obstetric and perinatal outcomes compared with controls. Infants with TGA have the best perinatal outcomes of all the CHD subcategories.